2022
DOI: 10.1111/his.14823
|View full text |Cite
|
Sign up to set email alerts
|

Loss of H3K27 trimethylation in a distinct group of de‐differentiated chordoma of the skull base

Abstract: De-differentiated chordoma with H3K27me3 loss 421

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 52 publications
(132 reference statements)
0
2
0
Order By: Relevance
“…Multiple studies have shown the importance of brachyury in the pathogenesis of chordoma [ 14 , 15 , 41 ]. However, some poorly differentiated and dedifferentiated chordoma display the loss of brachyury [ 42 , 43 ], SMARCB1/INI1 [ 44 , 45 ] or H3K27 trimethylation [ 46 ], TP53 mutation [ 42 ], and NF-ĸB activation [ 43 ]. These data suggest that the most common subtype of chordoma may potentially benefit from our VLP-delivered Cas9/gRNA RNP-based gene editing therapeutic approach, whereas poorly differentiated and dedifferentiated chordoma would not benefit from this approach.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have shown the importance of brachyury in the pathogenesis of chordoma [ 14 , 15 , 41 ]. However, some poorly differentiated and dedifferentiated chordoma display the loss of brachyury [ 42 , 43 ], SMARCB1/INI1 [ 44 , 45 ] or H3K27 trimethylation [ 46 ], TP53 mutation [ 42 ], and NF-ĸB activation [ 43 ]. These data suggest that the most common subtype of chordoma may potentially benefit from our VLP-delivered Cas9/gRNA RNP-based gene editing therapeutic approach, whereas poorly differentiated and dedifferentiated chordoma would not benefit from this approach.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have found that other methylation patterns in MPNST, such as dimethyl loss at H3K27, may be more specific when using immunohistochemistry [15]. Since its role in MPNST, H3K27me3 has been implicated in a number of different tumors for diagnostic and prognostic purpose, often associated with a poor prognosis or aggressive behavior, including rhabdomyosarcoma [16], chordoma [17], CNS tumors [18], amongst others.…”
Section: Introductionmentioning
confidence: 99%